Resiliensi Tunadaksa Terhadap Diskriminasi: Tinjauan Fenomenologi Di Yayasan Bunga Bali - Agustini, Putu Angelica; Krisna Aditya, I Gusti Ngurah Agung (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
D ifferently abled a re among the largest minority groups in the world who should be free from negative labeling, harassment, and humiliation. This research focuses on the resilience of d ifferently abled at the Bunga Bali Foundation. This research uses qualitative methods with observation, interviews, and a phenomenological approach to explore how the resilience of physical deficit overcomes social challenges and to see how actions are influenced by experiences, both past, present, and future. The subjects of this research consist of five individuals classified as having moderate to mild physical limitations, specifically those who use aids such as wheelchairs and crutches. The theoretical analysis used is the phenomenological concept according to Alfred Schütz, namely because-motives and in-order-to motives. The findings show that resilience plays an important role in helping d ifferently abled face and manage discrimination influenced by three factors. First, I Have (source of external support) from a role model obtained from family and peers at the foundation, as well as rules at the foundation that limit permissible and impermissible behaviors. Second, I Am (individual ability) which can demonstrate that the five informants are able to internalize the feeling that they are valuable individuals, full of potential, and responsible. Third, I Can (social and interpersonal skills) of the five informants have the ability to manage emotions and build trusting relationships with others. This research underscores the importance of understanding the life experiences of individuals with physical deficit and the need for improved accessibility and support systems in society. Keywords : because-motives; discrimination; phenomenology; in-order-to motives; resilience; physical deficit